An image processing method for morphology characterization and pitting corrosion evaluation - Codaro, E. N.; Nakazato, R. Z.; Horovistiz, A. L.; Ribeiro, LMF; Ribeiro, R. B.; Hein, LRO (Elsevier B.V., 2002)
A digital image processing and analysis method has been developed to classify shape and evaluate size and morphology parameters of corrosion pits. This method seems to be effective to analyze surfaces with low or high degree of pitting formation. Theoretical geometry data have been compared against experimental data obtained for titanium and aluminum alloys subjected to different corrosion tests. (C) 2002 Elsevier B.V. B.V. All rights reserved.
Keywords: pitting corrosion; metallography; image processing and analysis; shape descriptors